"The cell phone is free!": A study of the student’s propensity to Smartphone Dependence and the teacher’s perception in the classroom - Amorim, Rafael Machado; Corso , Kathiane Benedetti; Adão, Sebastiao Ailton da Rosa Cerqueira; Gaffrée , João Roberto de Lima; Araujo , Cristiane de Souza (Seven Editora, 2024)
The pedagogical practices of 30 years ago are incompatible with the current reality. The innovations provided using ICTs significantly reduce this time window. In view of this scenario, through a descriptive study, using the sequential mixed method, with quantitative and qualitative data collection, it was sought to meet the objective of the research, which is to analyze what are the effects of the use of the smartphone in the classroom on the student-teacher relationship in the Administration course of the Federal University of Pampa. From the application of the smartphone addiction test – SPAI-BR, the results indicate that about 43% of students can be considered smartphone dependent. With the qualitative stage of interviews with teachers, it was found that this group sometimes presents feelings of uselessness and lack of motivation in the teaching practice. However, they evaluate it as a good teaching tool, although little used in the classroom. Participant observation also showed that students commonly spend more time in the classroom attentive to what happens on social networks than in academic activity, collaborating even more to demotivate the teacher in pedagogical practice. The present work also brings as a contribution an analysis of the difficulties faced by teachers in the development of their activity and also presents the dichotomous reality between teachers and students’ smartphones. DOI:https://doi.org/10.56238/sevened2024.016-019